Pendred Syndrome: Clinical Manifestations, Diagnostic Strategies, and Nursing Management - Alotaibi, Lamia Naiaf; Merfat Mohammed Ali Alsaeed; Mona Moali Almotairi; Khadijah Mohamed Alessa; Elaf Nasser Almunayir; Abdullah Mohammed Musallam Alanazi; Nader Hammad Aldawsari; Layla Hassan Atiah Jarab; Ehsan Mohammed Mansor Junaid; Mishari Almutairi; Lamia Naiaf Alotaibi; Rasheed Mohammed Talaq Alotaibi (Saudi Journal of Medicine and Public Health, 2025)
Background: Pendred syndrome is a rare autosomal recessive disorder characterized by sensorineural hearing loss, thyroid abnormalities such as goiter, and inner ear malformations including an enlarged vestibular aqueduct and Mondini dysplasia. Its underlying cause is primarily pathogenic variants in the SLC26A4 gene, which impair pendrin function in the inner ear, thyroid, and renal epithelium. Aim: This study aims to summarize the clinical manifestations, diagnostic strategies, and comprehensive nursing management essential for optimizing outcomes in patients with Pendred syndrome. Methods: A detailed review of current clinical knowledge was conducted focusing on epidemiology, pathophysiology, diagnostic evaluation—including audiologic testing, thyroid assessment, imaging, and genetic analysis—and multidisciplinary management approaches. Results: Findings highlight that Pendred syndrome commonly presents during early childhood with bilateral, often progressive sensorineural hearing loss, exacerbated by minor trauma. Thyroid involvement typically manifests as euthyroid goiter during late childhood or adolescence, with some patients developing hypothyroidism. Inner ear anomalies such as enlarged vestibular aqueducts are characteristic and correlate with disease severity. Management is supportive, incorporating hearing aids or cochlear implantation, thyroid hormone replacement when needed, vestibular rehabilitation, and genetic counseling. Nursing plays a key role in education, monitoring, perioperative care, and longterm patient support. Conclusion: Early diagnosis, routine monitoring, and coordinated multidisciplinary care significantly improve communication, metabolic stability, and quality of life for affected individuals.